REGENERATIVE WATER MANAGEMENT ACROSS SCALES: A RETROFIT VISION FOR BIOSPHERE SUSTAINABILITY: Gestão regenerativa da água em todas as escalas: uma visão retrofit para a sustentabilidade da biosfera - Markelova, Ekaterina; Canals, Purificació; de Domingo, Angela; García-Durán Huet, Marc (Arquivos de Ciências do Mar, 2022)
There is a need for consistency in water management across scales and sectors, which motivated this paper to formulate a “proactive” retrofit vision seeking to integrate net-positive, sustainable and regenerative design concepts. Since the Planetary Boundaries framework is the key communication tool from scientific knowledge to political instruments (e.g., Sustainable Development Goals), water-related topics are revised accordingly. It is suggested that the role of water management in Climate Change is largely overlooked, which, in turn, is demonstrated to be the driver of change and, at the same time, impacted by these changes. Furthermore, it is demonstrated that the link between water-related carbon footprint and energy use presents the Climate Change community with a valuable opportunity to better manage two of the most valuable resources. A new approach is suggested by distinguishing water quality, quantity, and water state. So that beyond qualitative and quantitative goals, the physical state of water, which depends on hydrogen bonding, should help improve water management across scales. Understating water complexity shall facilitate communication raising awareness that every action creates a legacy. Overall, this study strengthens the idea that science-based strategies require better communication where biogeochemical science may serve a model to make knowledge more available to educators and policymakers. Keywords: water-related carbon footprint, molecular water structure, socio-ecological regeneration.